Physical and mechanical properties of thermoplastic composite from gliricidia sepium / Shaikh Abdul Karim Yamani - Yamani, Shaikh Abdul Karim (2011)
The study was conducted to determine the fiber morphology, density and the chemical properties of Gliricidia sepium concerning tree age. Thermoplastic composite boards of four variables: three tree ages (1,2 and 6 years old tree), four wood particles sizes (75U, 125^, 250|a and unscreen), three filler loadings (10, 30 and 50%), maleic anhydride grafted polypropylene (MAPP) additions unMAPP and 3% MAPP was manufactured and tested for tensile, impact, dimensional stability, bending properties conforming to the BS and ASTM standards. Scanning Electron Microscopy (SEM) of tensile test samples was performed to determine the bonding sites as evidence of bonding.